Characterization of B cells in lupus erythematosus skin biopsies in the context of different immune cell infiltration patterns - de Vos, Luka; Guel, Tugce; Niebel, Dennis; Bald, Sandra; ter Steege, Adrian; Bieber, Thomas; Wenzel, Joerg (Frontiers in Medicine, 2022)
Cutaneous lesions in lupus erythematosus (LE) subtypes are heterogenous. In line with the heterogeneity of the clinical presentation, the underlying lesional inflammation in LE skin samples is defined by different immune cell infiltrates. Pathophysiologically, lesional inflammation is driven by autoreactive cytotoxic T cells, targeting keratinocytes; plasmacytoid dendritic cells (pDCs), producing large amounts of interferon (IFN); and B cells, whose function in cutaneous LE is still unclear. This study aims to a) classify inflammatory patterns with regard to the dominating cell type or cytokine expression and b) investigating the specific role of B cells in LE skin lesions. Therefore, the immunohistological expression of inflammatory surrogates (CD20, CD123, MXA) in skin samples of n=119 LE (subtypes: subacute cutaneous LE, chronic discoid LE, chilblain LE, LE tumidus, other LE) and n=17 patients with inflammatory skin diseases (atopic dermatitis, psoriasis) were assessed. Samples were classified with regard to inflammatory groups. In addition multiplex-immunohistochemical analyses of n=17 LE skin samples focusing on lesional B cells were conducted. In this study, we show that cutaneous lesions present with eight different inflammatory groups dominated by B cells, pDCs, a strong IFN expression, or overlapping patterns. Altogether, LE subtypes show heterogenous infiltration regardless of LE subtype, certain subtypes display a preference for infiltration groups. Furthermore, lesional B cells either form diffuse infiltrates or pseudofollicular structures, wherein they show antigen-presenting and T cell-activating properties. Altogether, in the light of emerging targeted therapeutic options, we suggest histological assessment in regard to B-cell or pDC preponderance to allow tailored treatment decisions.